Amino acid neurotransmitters in sarcopenia and healthy aging - Steffi M. Jonk; James R. Tribble; Peter Swoboda; Pete A. Williams (Brain Research Bulletin)
Sarcopenia is the age-related degeneration of skeletal muscle. Healthy skeletal muscle secretes metabolites and macromolecules that are systemically important for the immune system (e.g. myokines) and the central nervous system (e.g. BDNF). Exercise interventions to stimulate skeletal muscle are therapeutic for sarcopenia and limit risk and/or provide neuroprotection in neurodegenerative disease models. Metabolic analysis of aged skeletal muscle has identified altered skeletal muscle metabolomes at an old age. Many of the molecules identified are amino acids that also act as neurotransmitters. In this review, we summarize how 13 amino acids act as neurotransmitters or as precursor to neurotransmitters, and how these are involved in the skeletal muscle secretome, sarcopenia, and (healthy) aging.